Metabolomic assessment of mechanisms underlying anti-renal fibrosis properties of petroleum ether extract from Amygdalus mongolica - Chen Gao; Wan-fu Bai; Hong-bing Zhou; Hai-mei Hao; Ying-chun Bai; Quan-li Liu; Hong Chang; Song-li Shi (Taylor & Francis Group, 2021)
Context The petroleum ether extract (PET) of Amygdalus mongolica (Maxim.) Ricker (Rosaceae) has an ameliorative effect on renal fibrosis (RF). Objective To evaluate the antifibrotic effects of A. mongolica seeds PET on RF by serum metabolomics, biochemical and histopathological analyses. Materials and methods Sixty male Sprague-Dawley rats were randomly divided into the sham-operated, RF model, benazepril hydrochloride-treated model (1.5 mg/kg) and PET-treated (1.75, 1.25, 0.75 g/kg) groups, and the respective drugs were administered intragastrically for 21 days. Biochemical indicators including BUN, Scr, HYP, SOD, and MDA were measured. Haematoxylin and eosin and Masson staining were used for histological examination. The serum metabolomic profiles were determined by UPLC-Q-TOF/MS and metabolism network analysis. Acute toxicity test was performed to validate biosafety. Results The PET LD50 was >23.9 g/kg in rats. PET significantly alleviated fibrosis by reducing the levels of Scr (from 34.02 to 32.02), HYP (from 403.67 to 303.17) and MDA (from 1.84 to 1.73), and increasing that of SOD (from 256.42 to 271.85). Metabolomic profiling identified 10 potential biomarkers, of which three key markers were significantly associated with RF-related pathways including phenylalanine, tyrosine and tryptophan biosynthesis, amino sugar and nucleotide sugar metabolism and tyrosine metabolism. In addition, three key biomarkers were restored to baseline levels following PET treatment, with the medium dose showing optimal effect. Conclusions These findings revealed the mechanism of A. mongolica PET antifibrotic effects for RF rats on metabolic activity and provided the experimental basis for the clinical application.